2021
DOI: 10.1002/msc.1586
|View full text |Cite
|
Sign up to set email alerts
|

A survey evaluation comparing pain curriculum taught in Australian exercise physiology degrees to graduate perceptions of their preparedness and competency to treat people with chronic pain

Abstract: Background and Aims This cross‐sectional study evaluated the nature of pain curriculum being taught in accredited exercise physiology degrees across Australian universities and its perceived usefulness for preparing exercise physiologists to treat people with chronic pain. Materials & Methods Universities and graduates were asked about the nature and sufficiency of pain curriculum taught, with particular emphasis on competencies for physical therapists as outlined by the International Association for the Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Together, the findings of this study and others demonstrate that adherence to guideline recommended treatments for CLBP is greater in those with higher biopsychosocial/lower biomedical beliefs (Alshehri et al., 2020; Bishop et al., 2008; Christe et al., 2021; Darlow et al., 2012; Gibbs et al., 2021). However, current evidence suggests that undergraduate pain curricula do not adequately address the biopsychosocial model of pain (Hoeger Bement & Sluka, 2015; Jones et al., 2022; Wideman et al., 2020), which, based on the findings of this study, may be associated with lower adherence to guideline concordant treatments. Indeed, it has been shown that further education can increase biopsychosocial beliefs (Gibbs et al., 2022; O’Sullivan et al., 2013), though the longitudinal effect on clinical decision‐making affecting people seeking care for CLBP is largely unknown.…”
Section: Discussionmentioning
confidence: 66%
“…Together, the findings of this study and others demonstrate that adherence to guideline recommended treatments for CLBP is greater in those with higher biopsychosocial/lower biomedical beliefs (Alshehri et al., 2020; Bishop et al., 2008; Christe et al., 2021; Darlow et al., 2012; Gibbs et al., 2021). However, current evidence suggests that undergraduate pain curricula do not adequately address the biopsychosocial model of pain (Hoeger Bement & Sluka, 2015; Jones et al., 2022; Wideman et al., 2020), which, based on the findings of this study, may be associated with lower adherence to guideline concordant treatments. Indeed, it has been shown that further education can increase biopsychosocial beliefs (Gibbs et al., 2022; O’Sullivan et al., 2013), though the longitudinal effect on clinical decision‐making affecting people seeking care for CLBP is largely unknown.…”
Section: Discussionmentioning
confidence: 66%